Educational inequality on the northern border of México: social reproduction and violence - Avila, Rocío (2022)
The persistence of educational actions and mechanisms that increase the exclusion of large groups affect not only school failure and dropout, but also impact low social mobility, an increase social conflicts, and the reproduction of inequality. This statement is contrasted in light of the analysis of indicators of students who completed secondary education in the state of Tamaulipas, Mexico, during 2019 and that illustrates the considerable gap between those who obtained insufficient levels and those who have high academic achievement. The results of the Planea standardized test carried out on 24,532 students were contrasted with socioeconomic, cultural and school modality variables, in addition, the variable of exposure to direct violence was incorporated in order to observe and describe how educational precariousness represents a form of structural violence, which widens the inequality gap, limits mobility and social development. The empirical findings show that there is a significant difference between different school groups, which allows establishing a certain degree of relationship between the context and academic achievement.